Nurses' perceptions of systems and hierarchies shaping their responses to child abuse and neglect. Issue 2 (3rd January 2020) - Lines, Lauren Elizabeth; Grant, Julian Maree; Hutton, Alison
Abstract: Nurses have an important role in preventing and responding to child abuse and neglect. This paper reports on nurses' perceptions of how organisational systems and hierarchies shaped their capacity to respond to child abuse and neglect. This is one of four key themes identified through an inductive analysis of data from a broader qualitative study that explored nurses' perceptions and experiences of keeping children safe. The study was guided by social constructionist theory, and data were collected through in‐depth interviews with nurses working with children in Australia ( n = 21). Key findings showed that nurses experienced many challenges to responding to child abuse, including difficulties sharing information, fear of making mistakes and inflexible systems of care. This was underpinned by an organisational 'rule‐centred' culture of following policies at the expense of maintaining an explicit focus on children's needs. These findings demonstrate first the importance of creative and flexible thinking from individual professionals, so policies are enacted with a clear child focus. Second, they highlight the need for leadership to enact organisational and systemic cultural change that maintains a genuinely child‐centred approach.